MANAJEMEN TALENTA APARATUR DESA UNTUK MENINGKATKAN PELAYANAN DI DESA SUMBULU, NIAS SELATAN - Bu’ulolo, Sanida (Jurnal Performa: Jurnal Manajemen dan Start-up Bisnis, 2025)
This study aims to examine the role of talent management in improving public services in Desa Sumbulu, Nias Selatan. Using a qualitative approach, this research employed in-depth interviews and document analysis to collect data from 20 village apparatus. The data were analyzed using thematic analysis to identify patterns and themes related to talent management practices. The findings suggest that effective talent management practices, including training and development, performance management, career development, and leadership development, are crucial in enhancing the skills and competencies of village apparatus, leading to improved public services. The study contributes to the development of village governments in Indonesia by highlighting the importance of investing in human resources to improve public services.